A kind of different shrinkage polyester low-elastic yarn and its preparation process

By adding Robu Lin fiber powder and modified organic bentonite loaded with magnesium oxide and far-infrared ceramic powder to heteroshrinkage polyester low-elastic wire, the problem of existing fibers lacking far-infrared emission function is solved, and the far-infrared emission function of the fiber is realized, expanding its application scenarios and meeting higher thermal insulation, health care and antibacterial needs.

CN119777023APending Publication Date: 2025-04-08ZHEJIANG HENGBAIHUA CHEMICAL FIBER CO LTD

Patent Information

Application Number
CN202510085898.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing heteroshrink polyester low-elastic wire lacks far-infrared emission function, which limits its applications in thermal insulation, health care and antibacterial aspects.

Method used

By adding Robulin fiber powder and modified organic bentonite to the fibers, and carrying magnesium oxide and far-infrared ceramic powder, and using esterification reaction and modification treatment processes, heteroshrink polyester low-elastic wire with far-infrared emission function was prepared.

Benefits of technology

It realizes the far-infrared emission function of fiber, expands its application scenarios in the fields of clothing, furniture, medical care and sports equipment, and meets higher thermal insulation, health care and antibacterial needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005250133860000111
    Figure BDA0005250133860000111
Patent Text Reader

Abstract

The present application relates to the field of textiles, and specifically discloses a kind of different shrinkage polyester low-elastic yarn and its preparation process, and its preparation process comprises the following steps: using aliphatic diol and aromatic acid as raw materials to carry out esterification reaction to obtain polyester raw materials; modifying the polyester raw materials with a regulator containing at least magnesium hydroxide whiskers and p-hydroxybenzoic acid to obtain primary modified polyester; mixing the primary modified polyester with apocynum fiber powder, modified organic bentonite and a compatibility promoter to carry out modification to obtain melt granulation to obtain modified polyester masterbatch; spraying the obtained modified polyester masterbatch and polyester chips from a convex-shaped spinneret hole, passing through an ultra-short windless zone under a spray washing plate, and then cooling and solidifying in a gradient-distributed uneven manner, and then undergoing low-temperature elasticization treatment to obtain different shrinkage polyester low-elastic yarn; the present application also discloses the different shrinkage polyester low-elastic yarn obtained by the above process, and the present application has the characteristics of having a far-infrared emission function on the basis of obtaining a single-component different shrinkage polyester low-elastic yarn.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of textiles, and more specifically, to a kind of differentially shrinkable polyester low-elastic yarn and a preparation process thereof. Background Art

[0002] Polyester low-stretch yarn is an important variety of polyester fiber. Due to its excellent wrinkle resistance, shape retention and comfort, it has been widely used in clothing, home textiles and other fields. With the technological progress and industrial upgrading of the textile industry, the production efficiency and product quality of polyester low-stretch yarn have been continuously improved, and the market demand has also shown a steady growth trend.

[0003] As a fiber with special properties, differential shrinkage polyester low-elastic yarn is a fiber with differential shrinkage due to different shrinkage rates. Due to its unique differential shrinkage properties, it can meet more diverse market demands, such as improving the elasticity and adaptability of fabrics. Currently, most differential shrinkage fibers on the market are made by plying two or three strands of filaments with different shrinkage rates.

[0004] At present, the research on different shrinkage polyester low-elastic yarn is disclosed in a Chinese patent with application publication number CN106400178A, which discloses a method for manufacturing different shrinkage polyester low-elastic yarn, which discloses that it includes the following steps: 1) mixing organic magnesium hydroxide whiskers, organic montmorillonite, organic barium sulfate nanopowder, ethylene glycol, propylene glycol, butylene glycol, p-hydroxybenzoic acid, and sodium germanate to prepare different shrinkage composite alcohol solution; 2) mixing organic wollastonite nano needle-shaped fibers, mica powder, polyethylene glycol, propylene glycol, butylene glycol, high-temperature antioxidant 1098, ethylene glycol antimony, and protonating agent phosphoric acid to prepare different shrinkage composite accelerator; 3) co-condensing the different shrinkage composite multifunctional alcohol solution, the different shrinkage composite accelerator, purified terephthalic acid, and ethylene glycol to prepare a different shrinkage modified polyester, the melt of which is ejected from a convex-shaped spinneret hole, and adopting a cooling and solidification method and a low-temperature elasticization process to obtain different shrinkage polyester low-elastic yarn. The above method realizes the production of single-component different shrinkage fiber.

[0005] There is also a Chinese patent application with publication number CN109537088A that discloses a method for manufacturing a low-elastic polyester yarn with different shrinkage, which includes the following steps: S1, preparation of modified polyester; S2, preparation of modified polyester masterbatch; S3, preparation of low-elastic polyester yarn with different shrinkage; S4, post-treatment of low-elastic polyester yarn with different shrinkage. The single-component low-elastic polyester yarn prepared by the above method solves the problem of dyeing difficulties and has the characteristics of high dyeing rate, uniform dyeing and good shrinkage performance.

[0006] At present, the research on shrinkage polyester low-elastic yarn is mainly about single component or its dyeing problem, and there are also a small number of studies on its antibacterial properties. With the advancement of science and technology and the increasing needs of human beings, far-infrared textiles are a kind of textiles with thermal insulation, health care, antibacterial and other functions. By adding ceramic powders with high far-infrared emissivity to the inside or surface of textiles, the textiles can not only absorb light in nature or far-infrared radiation from the human body, causing their own temperature to rise, but also emit far-infrared rays with wavelengths and powers corresponding to their temperature, so that the human body can obtain functions such as warmth preservation and temperature increase, and improve the human microcirculation system.

[0007] After the shrinkage polyester low-elastic yarn is processed to have far-infrared emission function, its application field will be greatly expanded. It can not only be used in the manufacture of traditional clothing and furniture, but also in medical, sports equipment and other fields. It has a wide range of application scenarios to meet the needs. Summary of the invention

[0008] In order to realize the far-infrared emission function of differentially shrinkable polyester low-elastic yarn, the present application provides a differentially shrinkable polyester low-elastic yarn and a preparation process thereof.

[0009] In the first aspect, the present application provides a process for preparing a polyester low-elastic yarn with different shrinkage, which adopts the following technical scheme: A process for preparing a polyester low-elastic yarn with different shrinkage, comprising the following steps: S1, using aliphatic diol and aromatic acid as raw materials to carry out esterification reaction to obtain polyester raw materials; S2, modifying the polyester raw material with a regulator containing at least magnesium hydroxide whiskers and p-hydroxybenzoic acid to obtain a primary modified polyester; S3, modifying the primary modified polyester by mixing with apocynum fiber powder, modified organic bentonite loaded with magnesium oxide and far-infrared ceramic powder, and a compatibility promoter to obtain a modified polyester masterbatch by melt granulation; S4. The prepared modified polyester masterbatch and polyester chips are sprayed out from the convex-shaped spinneret hole, passed through the ultra-short windless zone under the spray-washing plate, and then subjected to gradient distribution uneven cooling and solidification, and then subjected to low-temperature stretching treatment to obtain the differential shrinkage polyester low-elastic yarn.

[0010] By adopting the above technical scheme, in the present application, polyester particles are firstly prepared by esterification reaction, and then modified by a regulator containing magnesium hydroxide whiskers and p-hydroxybenzoic acid. Due to its special structure and properties, magnesium hydroxide whiskers can be used as heterogeneous nucleating agents for polyester crystallization. In the polyester melt, magnesium hydroxide whiskers provide additional nucleation sites, reduce the crystallization temperature of polyester, and accelerate the crystallization process. This nucleation effect helps to form smaller and more uniform polyester crystals, which may affect the shrinkage behavior of polyester, and the introduction of magnesium hydroxide whiskers may also change the structure of polyester crystals; p-hydroxybenzoic acid and modified polyester form a thermotropic liquid crystal copolyester, which affects the crystallization of polyester by affecting the polyester chain sequence structure, affects the stress difference of polyester fiber during cooling and solidification, and then cooperates with the subsequent gradient non-uniform cooling and solidification mode to make the fiber show different shrinkage behaviors during stretching and recovery, thereby forming a heterogeneous shrinkage effect, and finally obtains a single-component heterogeneous shrinkage polyester low-elastic yarn fiber.

[0011] In addition, in the present application, apocynum fiber powder and modified organic bentonite loaded with magnesium oxide are added to the modified polyester. As a natural far-infrared radiation material, apocynum fiber can emit far-infrared light waves. It contains rich flavonoids and polyphenol compounds. These molecules resonate in the fiber to emit far-infrared rays, activate cells, improve microcirculation, enhance immunity and delay aging, so that the prepared polyester low-elastic yarn has far-infrared emission function. In addition, apocynum fiber also has excellent antibacterial, anti-ultraviolet and moisture absorption and perspiration and other functions, giving the shrinkage polyester low-elastic yarn more functions to meet the needs of the present invention. In addition, the far-infrared ceramic powder in the modified organic bentonite loaded with magnesium oxide and far-infrared ceramic powder gives the polyester low-elastic yarn a far-infrared emission function. When the fiber is stimulated by external heat, the far-infrared ceramic powder can absorb and store heat, and then release it in the form of far-infrared rays. The added loading of magnesium oxide enhances the stability of the structure between the organic bentonite, thereby improving the emission efficiency of the far-infrared ceramic powder, and the addition of the compatibility promoter helps to improve the mixing uniformity and dispersion between the modified organic bentonite and the primary modified polyester and apocynum fiber powder, thereby improving the far-infrared emission function of the final overall fiber.

[0012] Optionally, the modified organic bentonite loaded with magnesium oxide and far-infrared ceramic powder is prepared by the following method: 1) Dispersing the far-infrared ceramic powder in a polyvinyl alcohol aqueous solution, adding organic bentonite, and then performing ultrasonic dispersion and impregnation treatment, filtering and drying to obtain pretreated organic bentonite loaded with far-infrared ceramic powder; 2) Pretreated organic bentonite is added to the magnesium acetate solution, and the solution is impregnated, dried, and then calcined to obtain modified organic bentonite loaded with far-infrared ceramic powder and magnesium oxide.

[0013] By adopting the above technical scheme, in the present application, the organic bentonite is first dispersed in a polyvinyl alcohol aqueous solution, and the far-infrared ceramic powder is loaded under the bonding effect of the polyvinyl alcohol. Then, the organic bentonite is immersed in a magnesium acetate solution and dried. Then, nano-magnesium oxide particles are formed under high-temperature roasting conditions and attached to the organic bentonite to load magnesium oxide and far-infrared ceramic powder. The organic bentonite is modified on the basis of bentonite and an organic chain is introduced so that it can interact with the functional groups in the polyester molecular chain, thereby enhancing the compatibility between the two. Moreover, the interlayer spacing of the organic bentonite is large, which is conducive to the insertion and dispersion of the polyester molecular chain, which not only helps to improve the compatibility between the two, but also affects the crystallization behavior of the polyester molecular chain, and helps to obtain fibers with better shrinkage performance.

[0014] Optionally, in the preparation process of the modified organic bentonite loaded with magnesium oxide and far-infrared ceramic powder, the addition mass ratio of far-infrared ceramic powder to organic bentonite is 1:(4-5), and the mass concentration of the polyvinyl alcohol aqueous solution is 5-10wt%, and the addition amount of the polyvinyl alcohol aqueous solution is 8-10 times that of the far-infrared ceramic powder; The mass concentration of the magnesium acetate solution is 15-25wt%, and the mass ratio of the added amount of the magnesium acetate solution to the added mass of the pretreated organic bentonite is 1:(6-8).

[0015] By adopting the above technical solution and controlling the above addition amount, the amount of organic bentonite loaded with far-infrared ceramic powder and the amount of nano magnesium oxide formed after calcination can be controlled, thereby affecting the subsequent shrinkage and far-infrared emission effects.

[0016] Optionally, in the preparation process of the modified organic bentonite loaded with magnesium oxide and far-infrared ceramic powder, the immersion temperature in step 1) is 55-65° C. and the immersion time is 30-40 min; In step 2), the impregnation temperature is 40-50° C., the impregnation time is 20-40 min, and the roasting temperature is 400-420° C., and the roasting time is 1-2 h.

[0017] Optionally, during the preparation of the modified organic bentonite loaded with magnesium oxide and far-infrared ceramic powder, γ-aminopropyltriethoxysilane is added at the same time as the far-infrared ceramic powder, and the added amount of γ-aminopropyltriethoxysilane is 5-10wt% of the far-infrared ceramic powder.

[0018] By adopting the above technical solution, the addition of silane coupling agent realizes the bonding between inorganic far-infrared ceramic powder and organic bentonite, and the chemical connection of far-infrared ceramic powder on organic bentonite is enhanced through chemical bonding, thereby improving its load stability and better playing its role.

[0019] Optionally, the compatibility promoter is a mixture of maleic anhydride grafted EVA and maleic anhydride grafted POE in a mass ratio of 1:(0.1-0.2).

[0020] By adopting the above technical scheme, a mixture of maleic anhydride grafted EVA and maleic anhydride grafted POE is selected as a compatibility promoter in the present application. The maleic anhydride grafted EVA has better compatibility with polyester due to the presence of ester groups, and maleic anhydride can also react with the hydroxyl functional groups in the apocynum fiber powder to improve the compatibility. The maleic anhydride grafted POE introduces strongly polar maleic anhydride side groups on the non-polar POE molecular main chain, which has a certain compatibility between polyester and apocynum fiber powder, thereby improving the compatibility of the mixed system, facilitating the uniform dispersion of apocynum fiber powder and modified organic bentonite in the primary modified polyester system, and ultimately achieving a better far-infrared emission function.

[0021] Optionally, the apocynum venetum fiber powder is soaked in a sodium hydroxide solution with a mass concentration of 5-8wt% for 10-25min, filtered and dried to obtain pretreated apocynum venetum fiber powder, which is then mixed with the primary modified polyester for modification.

[0022] By adopting the above technical scheme, the apocynum fiber powder is soaked in a sodium hydroxide solution and then added. On the one hand, the sodium hydroxide solution can dissolve and remove pectin and lignin in the apocynum fiber powder, and can make the apocynum fiber swell, improve its fiber structure, and affect the hygroscopicity and expansion type of the apocynum fiber powder, thereby affecting its shrinkage performance. In addition, the roughness of the apocynum fiber powder after sodium hydroxide treatment is increased, which can improve the sub-interface compatibility with polyester, thereby improving the compatibility of the apocynum fiber powder with polyester, helping to improve its uniform dispersion, improve the myocardial infarction of the modified polyester masterbatch, and will not affect the far-infrared emission performance and antibacterial properties, and ultimately improve the performance of the polyester low-elastic yarn.

[0023] Optionally, the aliphatic diol in step S1 includes one or more of ethylene glycol, 1,3-propylene glycol, 1,4-butanediol and 1,6-hexanediol; The aromatic acid includes one or more of terephthalic acid and isophthalic acid.

[0024] Optionally, the regulator in step S2 is prepared by the following method: In parts by weight, 0.5-3 parts of needle-shaped wollastonite fibers, 8-12 parts of magnesium hydroxide whiskers, 1-3 parts of polyethylene glycol, 4-8 parts of 1,3-propylene glycol, 6-12 parts of p-hydroxybenzoic acid, 1-3 parts of 1,4-butanediol, 0.5-2 parts of mica powder, 0.5-1.5 parts of 1,6-hexanediol and 0.3-0.8 parts of antimony ethylene glycol are mixed, stirred at 60-70° C., ground for 1-2 hours, dehydrated under vacuum to a water content of less than 1%, and kept warm for later use.

[0025] By adopting the above technical solution, the preparation and addition of the above regulator enables the prepared polyester fiber to have excellent shrinkage performance.

[0026] Optionally, the specific operation of the preparation process of the different shrinkage polyester low-elastic yarn is: In parts by weight, S1, 10-20 parts of terephthalic acid, 8-15 parts of ethylene glycol, 5-10 parts of 1,4-butanediol and 5-8 parts of isophthalic acid are mixed, 1-3 parts of a catalyst, 1-3 parts of polyethylene glycol and 1-3 parts of dimethyl phosphate are added, and the mixture is stirred and reacted at 240-260° C. and 0.06-0.08 MPa for 2-3 hours to obtain a polyester raw material; S2, taking 10-20 parts of the polyester raw material prepared in step S1, 2-5 parts of 1,2-dimethylpropylene glycol, 2-5 parts of polyethylene glycol and 5-8 parts of dimethyl isophthalate-5-sodium sulfonate, reacting them at 260-280° C. for 20-30 minutes, adding 3-7 parts of a regulator and continuing the reaction for 30-40 minutes to obtain a primary modified polyester; S3, taking 20-35 parts of the initially modified polyester obtained in step S2, 3-8 parts of apocynum fiber powder, 5-10 parts of modified organic bentonite loaded with magnesium oxide and far-infrared ceramic powder, and 2-6 parts of a compatibility promoter, mixing and stirring at 260-280° C., and then adding 1-3 parts of an antioxidant and 1-5 parts of a lubricant for melt granulation to obtain a modified polyester masterbatch; S4, the modified polyester wood and polyester chips in step S3 are melt-mixed in a mass ratio of 1: (0.4-0.5) and then ejected from a convex-shaped spinneret hole, passed through an ultra-short windless zone under a spray plate, and then subjected to a gradient-distributed uneven cooling and solidification method, and then subjected to a low-temperature elastic treatment to obtain a differentially shrinkable polyester low-elastic yarn.

[0027] In the second aspect, the present application provides a low-elastic polyester yarn with different shrinkage, which adopts the following technical solution: A different-shrinkage polyester low-elastic yarn is prepared by adopting the preparation process.

[0028] By adopting the above technical scheme, the polyester fiber obtained by the method provided by the present application is a single-component heterogeneous shrinkage fiber, which has excellent far-infrared emission function on the basis of the functions of heterogeneous crystallization, heterogeneous orientation and heterogeneous shrinkage, and meets the current more functional requirements for fiber materials.

[0029] In summary, this application has the following beneficial effects: 1. In the present application, polyester particles are firstly prepared by esterification reaction, and then modified by a regulator containing magnesium hydroxide whiskers and p-hydroxybenzoic acid, so as to affect the crystallization of polyester by affecting the sequence structure of polyester chains, thereby affecting the stress difference generated by polyester fibers during the cooling and solidification process, and then combined with the subsequent gradient non-uniform cooling and solidification method, the fibers exhibit different shrinkage behaviors during the stretching and recovery process, thereby forming a different shrinkage effect, and finally obtaining a single-component different shrinkage polyester low-elastic yarn fiber; 2. In the present application, apocynum fiber powder and modified organic bentonite loaded with magnesium oxide are added to the modified polyester. As a natural far-infrared radiation material, apocynum fiber can emit far-infrared light waves. It contains rich flavonoids and polyphenol compounds. These molecules resonate in the fiber to emit far-infrared rays, activate cells, improve microcirculation, enhance immunity and delay aging, so that the prepared polyester low-elastic yarn has far-infrared emission function. In addition, apocynum fiber also has excellent antibacterial, anti-ultraviolet and moisture absorption and perspiration and other functions, giving the shrinkage polyester low-elastic yarn more functions to meet the needs of the present invention. In addition, the far-infrared ceramic powder in the modified organic bentonite loaded with magnesium oxide and far-infrared ceramic powder gives the polyester low-elastic yarn a far-infrared emission function. When the fiber is stimulated by external heat, the far-infrared ceramic powder can absorb and store heat, and then release it in the form of far-infrared rays. The added loading of magnesium oxide enhances the stability of the structure between the organic bentonite, thereby improving the emission efficiency of the far-infrared ceramic powder, and the addition of the compatibility promoter helps to improve the mixing uniformity and dispersion between the modified organic bentonite and the primary modified polyester and apocynum fiber powder, thereby improving the far-infrared emission function of the final overall fiber. DETAILED DESCRIPTION

[0030] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.

[0031] In the following preparation examples, the far-infrared ceramic powder is selected from the far-infrared ceramic powder of Lingshou County Tuolin Mineral Products Processing Plant; The organic bentonite used is the organic bentonite model BP-183 produced by Zhejiang Huate New Materials Co., Ltd.

[0032] In the following examples, maleic anhydride grafted POE (POE-G-MAH) was selected from Dongguan Shangpin New Material Technology Co., Ltd. The American Dow brand is FUSABOND TM N416; Maleic anhydride grafted EVA (EVA-g-MAH) was selected from Bedahl (Ningbo) New Materials Co., Ltd. The brand is LyondellBasell, the model is PX1164, and the grade is Plexar EVA-g-MAH.

[0033] The following preparation example is a preparation example of modified organic bentonite loaded with magnesium oxide and far-infrared ceramic powder. A method for preparing modified organic bentonite comprises the following steps: 1) Dispersing the far-infrared ceramic powder in a polyvinyl alcohol aqueous solution, then adding organic bentonite and performing ultrasonic dispersion and impregnation treatment, the impregnation temperature is 60° C., the impregnation time is 35 min, then filtering and drying, to obtain pretreated organic bentonite loaded with far-infrared ceramic powder; The mass ratio of far-infrared ceramic powder to organic bentonite is 1:4.5, and the mass concentration of polyvinyl alcohol aqueous solution is 8wt%, and the amount of polyvinyl alcohol aqueous solution added is 9 times that of far-infrared ceramic powder. 2) Add pretreated organic bentonite to the magnesium acetate solution, immerse and dry it at a temperature of 45°C for 30 minutes, then calcine at a temperature of 410°C for 1.5 hours to obtain modified organic bentonite loaded with far-infrared ceramic powder and magnesium oxide.

[0034] The mass concentration of the magnesium acetate solution is 20wt%, and the mass ratio of the added amount of the magnesium acetate solution to the added mass of the pretreated organic bentonite is 1:7.

[0035] Preparation Example 2 A method for preparing modified organic bentonite comprises the following steps: 1) Dispersing the far-infrared ceramic powder in a polyvinyl alcohol aqueous solution, then adding organic bentonite and performing ultrasonic dispersion and impregnation treatment, the impregnation temperature is 55° C., the impregnation time is 40 min, then filtering and drying, to obtain pretreated organic bentonite loaded with far-infrared ceramic powder; The mass ratio of far-infrared ceramic powder to organic bentonite is 1:4, the mass concentration of polyvinyl alcohol aqueous solution is 5wt%, and the amount of polyvinyl alcohol aqueous solution added is 8 times that of far-infrared ceramic powder; 2) Add pretreated organic bentonite to the magnesium acetate solution, immerse it in water and dry it, the immersion temperature is 40°C, the immersion time is 40 minutes, and then roast it, the roasting temperature is 400°C, and the roasting time is 2 hours, to obtain modified organic bentonite loaded with far-infrared ceramic powder and magnesium oxide.

[0036] The mass concentration of the magnesium acetate solution is 15wt%, and the mass ratio of the added amount of the magnesium acetate solution to the added mass of the pretreated organic bentonite is 1:6.

[0037] Preparation Example 3 A method for preparing modified organic bentonite comprises the following steps: 1) Dispersing the far-infrared ceramic powder in a polyvinyl alcohol aqueous solution, then adding organic bentonite and performing ultrasonic dispersion and impregnation treatment, the impregnation temperature is 65° C., the impregnation time is 30 min, then filtering and drying, to obtain pretreated organic bentonite loaded with far-infrared ceramic powder; The mass ratio of far-infrared ceramic powder to organic bentonite is 1:5, the mass concentration of polyvinyl alcohol aqueous solution is 10wt%, and the amount of polyvinyl alcohol aqueous solution added is 10 times that of far-infrared ceramic powder; 2) Add pretreated organic bentonite to the magnesium acetate solution, immerse it in water and dry it, the immersion temperature is 50°C, the immersion time is 20min, and then roast it, the roasting temperature is 420°C, and the roasting time is 1h, to obtain modified organic bentonite loaded with far-infrared ceramic powder and magnesium oxide.

[0038] The mass concentration of the magnesium acetate solution is 25wt%, and the mass ratio of the added amount of the magnesium acetate solution to the added mass of the pretreated organic bentonite is 1:8.

[0039] Preparation Example 4 A method for preparing modified organic bentonite is carried out according to the method in Preparation Example 1, except that in step 1), γ-aminopropyltriethoxysilane is added together with far-infrared ceramic powder, and the amount of γ-aminopropyltriethoxysilane added is 8wt% of the far-infrared ceramic powder.

[0040] Preparation Example 5 A method for preparing modified organic bentonite is carried out according to the method in Preparation Example 1, except that in step 1), γ-aminopropyltriethoxysilane is added together with far-infrared ceramic powder, and the amount of γ-aminopropyltriethoxysilane added is 5wt% of the far-infrared ceramic powder.

[0041] Preparation Example 6 A method for preparing modified organic bentonite is carried out according to the method in Preparation Example 1, except that in step 1), γ-aminopropyltriethoxysilane is added together with far-infrared ceramic powder, and the amount of γ-aminopropyltriethoxysilane added is 10wt% of the far-infrared ceramic powder.

[0042] Comparative Preparation Example 1 A method for preparing modified organic bentonite is carried out according to the method in Preparation Example 1, except that step 2) is not performed, that is, the organic bentonite is only loaded with far-infrared ceramic powder.

[0043] Comparative Preparation Example 2 A method for preparing modified bentonite is carried out according to the method in Preparation Example 1, except that an equal amount of organic bentonite is replaced by bentonite.

[0044] Example 1 A method for preparing a different-shrinkage polyester low-elastic yarn comprises the following steps: S1, 15kg of terephthalic acid was mixed with 10kg of ethylene glycol, 8kg of 1,4-butanediol and 6kg of isophthalic acid, 2kg of antimony trioxide catalyst, 2kg of polyethylene glycol and 2kg of dimethyl phosphate were added, and the mixture was stirred and reacted at 250°C and 0.07MPa for 2.5h to obtain a polyester raw material; S2, 1.5kg of needle-shaped wollastonite fiber, 10kg of magnesium hydroxide whisker, 2kg of polyethylene glycol, 6kg of 1,3-propylene glycol, 10kg of p-hydroxybenzoic acid, 2kg of 1,4-butanediol, 1.2kg of mica powder, 1kg of 1,6-hexanediol and 0.5kg of antimony glycol were mixed, stirred at 65°C, ground for 1.5h, and then dehydrated under vacuum to a water content of less than 1% to obtain a regulator, which was kept warm for later use; 15 kg of the polyester raw material prepared in step S1 was reacted with 3 kg of 1,2-dimethylpropylene glycol, 3 kg of polyethylene glycol and 6 kg of sodium dimethyl 5-sulfonate at 270° C. for 25 min, and then 5 kg of the above-prepared regulator was added and the reaction was continued for 35 min to obtain a primary modified polyester; S3, taking 28 kg of the initially modified polyester obtained in step S2, 5 kg of apocynum fiber powder, 8 kg of the modified organic bentonite loaded with magnesium oxide and far-infrared ceramic powder obtained in Preparation Example 1, and 4 kg of a compatibility promoter, mixing and stirring at 270° C., adding 2 kg of antioxidant ascorbic acid and 2 kg of lubricant stearic acid amide for melt granulation, and obtaining a modified polyester masterbatch; Among them, the compatibility promoter is a mixture of maleic anhydride grafted EVA and maleic anhydride grafted POE in a mass ratio of 1:0.1; S4, the modified polyester wood in step S3 and the polyester chips are melt-mixed in a mass ratio of 1:0.45 and then sprayed out from the convex spinneret hole, passing through the ultra-short windless zone under the spray plate, and then subjected to a gradient distribution uneven cooling and solidification method, and then subjected to low-temperature elastic treatment to obtain the differential shrinkage polyester low-elastic yarn.

[0045] Example 2 A method for preparing a different-shrinkage polyester low-elastic yarn comprises the following steps: S1, 10kg of terephthalic acid was mixed with 8kg of ethylene glycol, 5kg of 1,4-butanediol and 5kg of isophthalic acid, 1kg of antimony trioxide catalyst, 1kg of polyethylene glycol and 1kg of dimethyl phosphate were added, and the mixture was stirred and reacted at 240°C and 0.06MPa for 3h to obtain a polyester raw material; S2, 0.5kg of needle-shaped wollastonite fiber, 8kg of magnesium hydroxide whisker, 1kg of polyethylene glycol, 4kg of 1,3-propylene glycol, 6kg of p-hydroxybenzoic acid, 1kg of 1,4-butanediol, 0.5kg of mica powder, 0.5kg of 1,6-hexanediol and 0.3kg of antimony glycol are mixed, stirred at 60°C, ground for 2h, and then dehydrated under vacuum to a water content of less than 1% to obtain a regulator, which is kept warm for later use; 10 kg of the polyester raw material prepared in step S1 was reacted with 2 kg of 1,2-dimethylpropylene glycol, 2 kg of polyethylene glycol and 5 kg of sodium dimethyl isophthalate-5-sulfonate at 260° C. for 30 min, and then 3 kg of the above-prepared regulator was added and the reaction was continued for 30 min to obtain a primary modified polyester; S3, taking 20 kg of the initially modified polyester obtained in step S2, 3 kg of apocynum fiber powder, 5 kg of the modified organic bentonite loaded with magnesium oxide and far-infrared ceramic powder obtained in Preparation Example 2, and 2 kg of a compatibility promoter, mixing and stirring at 260° C., adding 1 kg of an antioxidant ascorbic acid and 1 kg of a lubricant stearic acid amide for melt granulation, and obtaining a modified polyester masterbatch; Among them, the compatibility promoter is a mixture of maleic anhydride grafted EVA and maleic anhydride grafted POE in a mass ratio of 1:0.1; S4, the modified polyester wood in step S3 and the polyester chips are melt-mixed in a mass ratio of 1:0.4 and then sprayed out from a convex-shaped spinneret hole, passed through an ultra-short windless zone under the spray plate, and then subjected to a gradient-distributed uneven cooling and solidification method, and then subjected to a low-temperature elastic treatment to obtain a different-shrinkage polyester low-elastic yarn.

[0046] Example 3 A method for preparing a different-shrinkage polyester low-elastic yarn comprises the following steps: S1, 20kg of terephthalic acid was mixed with 15kg of ethylene glycol, 10kg of 1,4-butanediol and 8kg of isophthalic acid, 3kg of antimony trioxide catalyst, 3kg of polyethylene glycol and 3kg of dimethyl phosphate were added, and the mixture was stirred and reacted at 260°C and 0.08MPa for 2h to obtain a polyester raw material; S2, 3kg of needle-shaped wollastonite fiber, 12kg of magnesium hydroxide whisker, 3kg of polyethylene glycol, 8kg of 1,3-propylene glycol, 12kg of p-hydroxybenzoic acid, 3kg of 1,4-butanediol, 2kg of mica powder, 1.5kg of 1,6-hexanediol and 0.8kg of antimony glycol were mixed, stirred at 70°C, ground for 1h, and then dehydrated under vacuum to a water content of less than 1% to obtain a regulator, which was kept warm for later use; 20 kg of the polyester raw material prepared in step S1 was reacted with 5 kg of 1,2-dimethylpropylene glycol, 5 kg of polyethylene glycol and 8 kg of sodium dimethyl 5-sulfonate at 280° C. for 20 min, and then 7 kg of the above-prepared regulator was added and the reaction was continued for 40 min to obtain a primary modified polyester; S3, taking 35 kg of the initially modified polyester obtained in step S2, 8 kg of apocynum fiber powder, 10 kg of the modified organic bentonite loaded with magnesium oxide and far-infrared ceramic powder obtained in Preparation Example 3, and 6 kg of a compatibility promoter, mixing and stirring at 280° C., adding 3 kg of antioxidant ascorbic acid and 5 kg of lubricant stearic acid amide for melt granulation, and obtaining a modified polyester masterbatch; Among them, the compatibility promoter is a mixture of maleic anhydride grafted EVA and maleic anhydride grafted POE in a mass ratio of 1:0.2; S4, the modified polyester wood in step S3 and the polyester chips are melt-mixed in a mass ratio of 1:0.5 and then sprayed out from the convex spinneret hole, passing through the ultra-short windless zone under the spray plate, and then subjected to a gradient distribution uneven cooling and solidification method, and then subjected to low-temperature elastic treatment to obtain the differential shrinkage polyester low-elastic yarn.

[0047] Embodiment 4-6 A process for preparing a different shrinkage polyester low-elastic yarn is carried out according to the method in Example 1, except that the modified organic bentonite in step S3 is the modified organic bentonite prepared in Preparation Examples 4-6.

[0048] Example 7 A preparation process of different shrinkage polyester low-elastic yarn is carried out according to the method in Example 1, except that the apocynum fiber powder in step S3 is soaked in a sodium hydroxide solution with a mass concentration of 5wt% for 25 minutes and then filtered and dried to obtain pretreated apocynum fiber powder, which is then added and mixed with the primary modified polyester for modification.

[0049] Example 8 A preparation process of different shrinkage polyester low-elastic yarn is carried out according to the method in Example 1, except that the apocynum fiber powder in step S3 is soaked in a sodium hydroxide solution with a mass concentration of 8wt% for 10 minutes and then filtered and dried to obtain pretreated apocynum fiber powder, which is then added and mixed with the primary modified polyester for modification.

[0050] Comparative Example 1 A process for preparing a different shrinkage polyester low-elastic yarn is carried out according to the method in Example 1, except that the modified organic bentonite in step S3 is the modified organic bentonite prepared in Comparative Preparation Example 1.

[0051] Comparative Example 2 A process for preparing a different shrinkage polyester low-elastic yarn is carried out according to the method in Example 1, except that the modified organic bentonite in step S3 is replaced by the modified bentonite in comparative preparation example 2 in equal amounts.

[0052] Comparative Example 3 A process for preparing a different-shrinkage polyester low-elastic yarn is carried out according to the method in Example 1, except that in step S3, an equal amount of apocynum fiber powder is replaced by modified organic bentonite.

[0053] Comparative Example 4 A process for preparing a different-shrinkage polyester low-elastic yarn is carried out according to the method in Example 1, except that no compatibility promoter is added in step S3.

[0054] Performance Testing The different-shrinkage polyester low-elastic yarn prepared in the examples and comparative examples of the present application was woven to obtain a textile sample, and then the far-infrared emissivity relative to the black body in the far-infrared emission region was measured at 37°C using an FT-IR spectrometer in combination with GB / T30127-2013 "Testing and Evaluation of Far-Infrared Performance of Textiles", and the far-infrared radiation temperature rise performance was tested. The test results are shown in Table 1 below.

[0055] Table 1: Performance Testing Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Far infrared emissivity 0.895 0.887 0.889 0.915 0.908 0.913 Temperature rise / ℃ 12.1 10.8 11.3 15.8 15.2 15.5 Performance Testing Example 7 Example 8 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Far infrared emissivity 0.919 0.923 0.863 0.814 0.871 0.832 Temperature rise / ℃ 16.1 16.3 4.8 2.6 5.8 3.4 Referring to the test results in Table 1 above, the far-infrared emissivity of the sample obtained by spinning the fiber obtained in the embodiment of the present application is not less than 0.88, and the far-infrared radiation temperature rise is higher than 5°C, and the fiber obtained in the embodiment of the present application has a far-infrared emission function. Referring to the test results of Example 1 and Examples 4-6, when preparing the modified organic bentonite, γ-aminopropyltriethoxysilane is also added, which helps the firmness of the far-infrared ceramic powder loaded in the organic bentonite, so that it is evenly dispersed in the polyester system with the organic bentonite, and plays a better far-infrared emission function. Combined with the test results of Examples 7 and 8, soaking the apocynum fiber powder in sodium hydroxide solution helps to improve its compatibility with polyester, thereby improving the far-infrared emission performance.

[0056] Combined with the test results of Example 1 and Comparative Example 1, when the organic bentonite in Comparative Example 1 was modified without loading nano-magnesium oxide, its far-infrared performance was reduced. Combined with the test results of Comparative Example 2, when the organic bentonite was replaced with bentonite, the compatibility with the polyester system was affected, and its performance was significantly reduced. Combined with the test results of Comparative Example 4, when the compatibility promoter was not added, its far-infrared performance was also reduced. Combined with the test results of Comparative Example 3, when the apocynum fiber powder was not added, its far-infrared emission performance was reduced.

[0057] In addition, the fibers obtained in Example 1, Example 4, Example 8 and the comparative example of this application were prepared according to GB / T14344-2022 "Test method for tensile properties of chemical fiber filaments" to obtain different-shrinkage polyester low-elastic yarns, and multiple low-elastic yarns were combined into test strips with a width of 20 mm and a length of 300 mm. The breaking strength and elongation at break of the above-mentioned samples were tested along the length direction, and the test results are shown in Table 2 below.

[0058] Table 2: Combined with the test results in Table 2 above, the fiber prepared in the examples of the present application has excellent mechanical properties.

[0059] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A process for preparing a low-elastic polyester yarn with different shrinkage, characterized in that: The following steps are involved: S1, using aliphatic diol and aromatic acid as raw materials to carry out esterification reaction to obtain polyester raw materials; S2, modifying the polyester raw material with a regulator containing at least magnesium hydroxide whiskers and p-hydroxybenzoic acid to obtain a primary modified polyester; S3, modifying the primary modified polyester by mixing with apocynum fiber powder, modified organic bentonite loaded with magnesium oxide and far-infrared ceramic powder, and a compatibility promoter to obtain a modified polyester masterbatch by melt granulation; S4. The prepared modified polyester masterbatch and polyester chips are sprayed out from the convex-shaped spinneret hole, passed through the ultra-short windless zone under the spray-washing plate, and then subjected to gradient distribution uneven cooling and solidification, and then subjected to low-temperature stretching treatment to obtain the differential shrinkage polyester low-elastic yarn.

2. The process for preparing the differentially shrinkable polyester low-elastic yarn according to claim 1, characterized in that: The modified organic bentonite loaded with magnesium oxide and far-infrared ceramic powder is prepared by the following method: 1) Dispersing the far-infrared ceramic powder in a polyvinyl alcohol aqueous solution, adding organic bentonite, and then performing ultrasonic dispersion and impregnation treatment, filtering and drying, to obtain pretreated organic bentonite loaded with far-infrared ceramic powder; 2) Add pretreated organic bentonite to the magnesium acetate solution, immerse it in water, dry it, and then calcine it to obtain modified organic bentonite loaded with far-infrared ceramic powder and magnesium oxide.

3. The process for preparing the differentially shrinkable polyester low-elastic yarn according to claim 2, characterized in that: In the preparation process of the modified organic bentonite loaded with magnesium oxide and far-infrared ceramic powder, the addition mass ratio of far-infrared ceramic powder to organic bentonite is 1:(4-5), and the mass concentration of polyvinyl alcohol aqueous solution is 5-10wt%, and the addition amount of polyvinyl alcohol aqueous solution is 8-10 times that of far-infrared ceramic powder; The mass concentration of the magnesium acetate solution is 15-25wt%, and the mass ratio of the added amount of the magnesium acetate solution to the added mass of the pretreated organic bentonite is 1:(6-8).

4. The process for preparing the differentially shrinkable polyester low-elastic yarn according to claim 2, characterized in that: In the preparation process of the modified organic bentonite loaded with magnesium oxide and far-infrared ceramic powder, the immersion temperature in step 1) is 55-65° C. and the immersion time is 30-40 min; In step 2), the impregnation temperature is 40-50°C, the impregnation time is 20-40 minutes, and the roasting temperature is 400-420°C, and the roasting time is 1-2 hours.

5. The process for preparing the differentially shrinkable polyester low-elastic yarn according to claim 2, characterized in that: During the preparation of the modified organic bentonite loaded with magnesium oxide and far-infrared ceramic powder, γ-aminopropyltriethoxysilane is added while adding the far-infrared ceramic powder, and the added amount of γ-aminopropyltriethoxysilane is 5-10wt% of the far-infrared ceramic powder.

6. The process for preparing the differentially shrinkable polyester low-elastic yarn according to claim 1, characterized in that: The compatibility promoter is a mixture of maleic anhydride grafted EVA and maleic anhydride grafted POE in a mass ratio of 1:(0.1-0.2).

7. The process for preparing the differentially shrinkable polyester low-elastic yarn according to claim 1, characterized in that: The apocynum venetum fiber powder is soaked in a sodium hydroxide solution with a mass concentration of 5-8wt% for 10-25min, filtered and dried to obtain pretreated apocynum venetum fiber powder, which is then mixed with the primary modified polyester for modification.

8. The process for preparing the differentially shrinkable polyester low-elastic yarn according to claim 1, characterized in that: In step S1, the aliphatic diol includes one or more of ethylene glycol, 1,3-propylene glycol, 1,4-butanediol and 1,6-hexanediol; The aromatic acid includes one or more of terephthalic acid and isophthalic acid; The regulator in step S2 is prepared by the following method: In parts by weight, 0.5-3 parts of needle-shaped wollastonite fibers, 8-12 parts of magnesium hydroxide whiskers, 1-3 parts of polyethylene glycol, 4-8 parts of 1,3-propylene glycol, 6-12 parts of p-hydroxybenzoic acid, 1-3 parts of 1,4-butanediol, 0.5-2 parts of mica powder, 0.5-1.5 parts of 1,6-hexanediol and 0.3-0.8 parts of antimony ethylene glycol are mixed, stirred at 60-70° C., ground for 1-2 hours, dehydrated under vacuum to a water content of less than 1%, and kept warm for later use.

9. The process for preparing the differentially shrinkable polyester low-elastic yarn according to claim 1, characterized in that: The specific operation of the preparation process of different shrinkage polyester low-elastic yarn is: In parts by weight, S1, 10-20 parts of terephthalic acid, 8-15 parts of ethylene glycol, 5-10 parts of 1,4-butanediol and 5-8 parts of isophthalic acid are mixed, 1-3 parts of a catalyst, 1-3 parts of polyethylene glycol and 1-3 parts of dimethyl phosphate are added, and the mixture is stirred and reacted at 240-260° C. and 0.06-0.08 MPa for 2-3 hours to obtain a polyester raw material; S2, taking 10-20 parts of the polyester raw material prepared in step S1, 2-5 parts of 1,2-dimethylpropylene glycol, 2-5 parts of polyethylene glycol and 5-8 parts of dimethyl isophthalate-5-sodium sulfonate, reacting them at 260-280° C. for 20-30 minutes, adding 3-7 parts of a regulator and continuing the reaction for 30-40 minutes to obtain a primary modified polyester; S3, taking 20-35 parts of the initially modified polyester obtained in step S2, 3-8 parts of apocynum fiber powder, 5-10 parts of modified organic bentonite loaded with magnesium oxide and far-infrared ceramic powder, and 2-6 parts of a compatibility promoter, mixing and stirring at 260-280° C., and then adding 1-3 parts of an antioxidant and 1-5 parts of a lubricant for melt granulation to obtain a modified polyester masterbatch; S4, the modified polyester wood and polyester chips in step S3 are melt-mixed in a mass ratio of 1: (0.4-0.5) and then ejected from a convex-shaped spinneret hole, passed through an ultra-short windless zone under a spray plate, and then subjected to a gradient-distributed uneven cooling and solidification method, and then subjected to a low-temperature elastic treatment to obtain a differentially shrinkable polyester low-elastic yarn.

10. A polyester low-elastic yarn with different shrinkage obtained by the preparation process as described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Manufacturing method of different shrinkage polyester draw texturing yarn

    CN106400178A

  • Production method of different-shrinkage polyester drawn textured yarns

    CN109537088A

Cited By

  • High-adhesive-force modified copolyester hot melt adhesive and one-step in-situ modification preparation process thereof

    CN121319843A